Turf Toe Review. Issue 2 (April 2020) - Chiou, Daniel; Stupay, Kristen L.; Waryasz, Gregory
Turf toe is a term used to describe myriad injuries to the metatarsophalangeal complex of the great toe, which have been associated with the introduction of artificial turf surfaces in sport. If not diagnosed early and treated properly, these injuries can result in chronic pain and loss of mobility. Accurate injury grading through physical exam and advanced imaging is essential to guide treatment, thereby minimizing long-term complications and maximizing an athlete's recovery and return to play. Levels of Evidence: Level V